DEVELOPMENT OF A MOODLE-BASED LEARNING MANAGEMENT SYSTEM (LMS) TO IMPROVE STUDENT MOTIVATION AND LEARNING OUTCOMES - Izzudin Mukhadzib; Herman Dwi Surjono (JURNAL EDUSCIENCE, 2026)
Purpose – This research and development aims to 1 develop a Moodle-based LMS system for Geography that is feasible, 2 determine the practicality of LMS in learning, and 3 test the effectiveness of LMS in improving learning outcomes and motivation of grade XII students at SMAN 1 Tanjunganom.Methodology – The research used the Alessi and Trollip (2001) development model with three stages: planning, design, and development. This study employs a descriptive mixed-methods analysis (qualitative and quantitative). Product testing included alpha testing by 4 experts and beta testing in a small group (5 students and 1 teacher) and a large group (31 students and 1 teacher). Effectiveness data were obtained from the control class XII-9 and the experimental class XII-8, each with 35 students.Findings – The results showed that 1. the LMS was very feasible based on the assessments of subject matter experts 4.45 and media experts 4.54, 2. the LMS was practical based on the responses of students 2.60 and teachers 4.69, 3 LMS is effective in improving learning outcomes with a higher n-gain in the experimental class than in the control class 0.760.47 and a Sig. With a value of 0.001, 4 LMS is effective in increasing learning motivation, with a higher n-gain in the experimental class (0.510.36) and a Sig. value of 0.013.Contribution – Thus, the Moodle-based LMS effectively improves Geography learning outcomes and motivation for grade XII students at SMAN 1 Tanjunganom. This study offers a replicable model for Indonesian high schools implementing the Merdeka Curriculum, providing edtech evidence and practical guidelines for integrating digital maps and simulations in resource-limited settings.